Alterations in the gustatory papillae after anterior bite plate insertion in growing rats - Roody Beauboeuf; Ippei Watari; Eri Saito; Hsu Jui-Chin; Mariko Kubono-Mizumachi; Takashi Ono (Wolters Kluwer Medknow Publications, 2019)
OBJECTIVES: To determine whether the modification of dental occlusion, without molar extraction, affected the gustatory papillae located in the tongue of growing rats. MATERIALS AND METHODS: Five-week-old male Wistar rats were randomly divided into an anterior bite plate (ABP) group and a control group. Under general anesthesia, ABPs were placed on the occlusal surfaces of the maxillary incisors, while metal caps covered the mandibular incisal edges of the rats in the ABP group. The control group rats underwent a sham operation. The rats in both groups were euthanized 14 days after the procedure. The circumvallate papillae and taste buds were analyzed by immunohistochemical methods, and the fungiform papillae were observed and counted after immersion of the tongue in 1% methylene blue. RESULTS: Two weeks after ABP insertion and mandibular incisal cap placement, the gustatory papillae exhibited morphological and structural changes. The rats in the ABP group had exhibited significantly fewer fungiform papillae, and narrower circumvallate papillae, with greater trench depths, larger trench profile areas, smaller taste bud profile areas, lower ratios of the taste bud profile area to the trench profile area, and more taste buds than those in the control group. CONCLUSIONS: Our findings support the association between occlusal and taste functions and provide a basis for further studies on the gustatory function. In conclusion, loss of molar occlusion, resulting from the ABP and metal cap insertion, altered the peripheral gustatory receptors in the growing rats.